Synthesis of multicolored photoluminescent carbon nanodots and applications to secured tags in anti-counterfeiting, traceability and digital passport product - Aïssatou Coumba Sow; Etienne Palleau; Isabelle Fabre–Francke; Nicolas Ratel-Ramond; Cécile Marcelot; Laurence Ressier (Carbon Trends)
With the objective of achieving better product traceability, generating digital passport product and combating counterfeiting, we demonstrate a fully bio-sourced approach featuring photoluminescent carbon nanodot-based tags. A straightforward synthesis procedure is first developed, whereby multicolored photoluminescent colloidal carbon nanodots are obtained from coffee grounds through a process of carbonization and solid-liquid extraction. Carbon-based nanoparticles are indeed renowned for their minimal cytotoxicity, photochemical stability, environmental durability and ease of surface functionalization. A versatile tagging process is then proposed, whereby a drop of synthesized carbon nanodot-based bio-resist is directly deposited onto the surface to be marked. The surface is then structured into the shape of patterns of interest by means of a technique derive from UV microprinting. In order to enhance security and tracking capabilities, the obtained marking patterns can incorporate supplementary coded information, such as alphanumeric codes, QR codes, barcodes, and so forth. The mechanical and optical robustness of the obtained bio-sourced secured tags is demonstrated through various concrete use cases, which illustrate their suitability for use as both graphic identification elements and serializable data elements, particularly in the aerospace sector.